The Implementation of Environmental Education at Pondok Pesantren Nurul Hakim Kediri, West Lombok - Murdianto Murdianto (Edumaspul: Jurnal Pendidikan, 2022)
This research examines the implementation of environmental education at Pondok Pesantren Nurul Hakim Kediri, West Lombok. Environmental education has become increasingly important to be applied in Islamic educational institutions to shape an environmentally conscious generation. This case study employs a qualitative approach, utilizing interviews, observations, and document analysis. The research findings show that Pondok Pesantren Nurul Hakim has integrated environmental education concepts into the curriculum and daily activities of the students. Programs such as waste management, organic farming, and water conservation have become integral parts of education at this pesantren. These findings highlight the importance of a holistic approach to environmental education in Islamic educational institutions. However, challenges such as limited resources and lack of teacher training are still faced in its implementation. This study concludes that the integration of environmental education in pesantren can significantly contribute to shaping students' environmental awareness.